Persistent cloaca: persistence of the challenge - Amr Abdelhamid AbouZeid; Ahmed Bassiouny Radwan; Mohamed Eldebeiky; Sameh Abdel Hay (SpringerOpen, 2020)
Abstract Background Persistent cloaca or cloacal anomalies represent a special category of anorectal anomalies affecting the female sex with a reported incidence of about one in 25,000 live birth. The study included 34 cases of cloaca that were managed at our unit between 2003 through 2017. We retrospectively reviewed patients' records that included clinical presentation, investigations, operative data, and follow-up notes. Anatomically, we stratified cloaca into three types according to the level of urogenital confluence. A low confluence (type 1) was defined by being at or below the level of the lower border of pubic symphysis with a short common channel (11 cases). A high confluence (type 3) was defined by being at or above the level of the upper border of pubic symphysis (9 cases). Between the low and high types, we defined an intermediate type (type 2) where the urogenital confluence was behind the mid-portion of pubic symphysis (14 cases). Results Renal anomalies were common association: solitary kidney in seven, pelvic kidney in two, and urinary tract dilatation (hydroureteronephrosis) in 12 cases. At follow-up, chronic renal insufficiency was detected in seven cases The prognosis for urinary continence was excellent in low confluence (type 1) cloaca. On the other hand, urinary incontinence was common among type 3 (high confluence) cloaca (62.5%). Conclusion Renal anomalies represent a common association with cloaca and a major cause of morbidity. Efforts should be directed to preserve renal function during the initial management, and to preserve the continence potential following the definitive repair. Level of evidence This is a case series with no comparison group (level IV).